At the Heart of Learning (Series: Paper 2 of 4): Witulya Mulapa nganana Mantjintjaku: From Cultural Devastation to Cultural Re-Invention. Issue 1 (March 2014) - Minutjukur, Makinti; Osborne, Sam
For remote Central Australian Aboriginal communities, the world has changed completely and irrevocably in the space of a lifetime. Drawing on Jonathan Lear's (2006) Radical Hope, the authors highlight the comparative struggles outlined in Lear's reflection on the life of Crow Indian chief Plenty Coups. For An angu (Pitjantjatjara/Yankunytjatjara people), the same question that confronted Plenty Coups arises: "How can An angu pursue a 'virtuous' An angu existence in a world where 'being An angu' no longer 'makes any sense'?" The authors explore the possibilities of choosing cultural re-invention over resigning to a sense of "the end" and consider how the recognition and retention of long-held values might benefit the broader experience of education, rather than be considered as a barrier or constraint to "success".